Secularism Soviet style : teaching atheism and religion in a Volga republic - Luehrmann, Sonja (New anthropologies of Europe., 2011)
Sonja Luehrmann explores the Soviet atheist effort to build a society without gods or spirits and its afterlife in post-Soviet religious revival. Combining archival research on atheist propaganda of the 1960s and 1970s with ethnographic fieldwork in the autonomous republic of Marij El in Russia's Volga region, Luehrmann examines how secularist culture-building reshaped religious practice and interreligious relations. One of the most palpable legacies of atheist propaganda is a widespread didactic orientation among the population and a faith in standardized programs of personal transformation a.